Pelatihan pada kader tentang skrining perkembangan anak - Heni Puji Wahyuningsih; Siti Tyastuti (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
Toddler is a golden period. In infancy, the development of language skills, creativity, social awareness, emotional, and intelligence runs fast and is the foundation for further development. Children constitute the largest proportion of the population in Indonesia at 33.9% (82.6 million). Research in Indonesia shows that 20-30% of children under five experience growth disorders. The target of achieving the MDGs in 2015 has not been achieved, so hard work is needed to achieve this target. Community empowerment needs to be done so that these targets can be achieved. Health cadres are partners who are closer to the community. For this reason, it is necessary to create a quality of life for toddlers, to maintain and detect child development well, so that skilled cadres are needed to screen children. To achieve this, training of cadres on screening / checking of child development is carried out. Community service activities are carried out in stages with the stages of identification, implementation, monitoring, evaluation. This activity was held in September and October 2019. The facility needed was the KPSP booklet (Pre-Screening Development Questionnaire). Community service activities carried out in the form of training for cadres toddlers. Provision of material tailored to the needs of toddlers cadres. From the results of the evaluation conducted after the training was conducted, 85% of cadres were able to screen toddlers, but there were still some cadres who did not understand how to screen for child development so they needed to exercise routinely. Based on the results of the activities it can be concluded that the community has good enthusiasm so that the community service activities can run smoothly.